Nadwatul Ulama and Its Role in Defending Islamic Thought Against Colonial and Secular Influences - H.M. Ataur Rahman Nadwi (Bulletin of Islamic Research, 2025)
The intended goal of establishing the ‘Nadwatul Ulama’ Lucknow, India was to ignite the light of Islam throughout the world, by spreading the spirit and ideas of Islam among all people through the Islamic call, guided by wisdom, good advice, sound logic, and the modern era. It also aimed to protect Islam from all forms of suspicion and to dispel the doubts that had been raised about it due to dangerous propaganda and accusations directed against it, such as, the enemies of Islam, at the top of whose list are Christian and Jewish Orientalists and other missionaries who were directed towards it under the shadow of Western colonialism by distorting Islam and confusing the thoughts of Muslims by spreading the secular, irreligious idea in Islamic society. By indoctrinating the new generation of Muslims with deviant Western ideas, including Freudianism, Darwinism, existentialism, materialism, communism, atheism, and others, in this article we aim to clarify the desired objectives of establishing the 'Nadwatul Ulama' and briefly outline its role in achieving these desired objectives.